HIPP1 stabilizes the interaction between CP190 and Su(Hw) in the Drosophila insulator complex - Melnikova, Larisa (Sci Rep, 2019)
Suppressor of Hairy-wing [Su(Hw)] is one of the best characterized architectural proteins in Drosophila and recruits the CP190 and Mod(mdg4)-67.2 proteins to chromatin, where they form a well-known insulator complex. Recently, HP1 and insulator partner protein 1 (HIPP1), a homolog of the human co-repressor Chromodomain Y-Like (CDYL), was identified as a new partner for Su(Hw). Here, we performed a detailed analysis of the domains involved in the HIPP1 interactions with Su(Hw)-dependent complexes. HIPP1 was found to directly interact with the Su(Hw) C-terminal region (aa 720–892) and with CP190, but not with Mod(mdg4)-67.2. We have generated Hipp1 null mutants (Hipp(Δ1)) and found that the loss of Hipp1 does not affect the enhancer-blocking or repression activities of the Su(Hw)-dependent complex. However, the simultaneous inactivation of both HIPP1 and Mod(mdg4)-67.2 proteins resulted in reduced CP190 binding with Su(Hw) sites and significantly altered gypsy insulator activity. Taken together, these results suggested that the HIPP1 protein stabilized the interaction between CP190 and the Su(Hw)-dependent complex.